Development of interactive learning media assisted by Padlets on the theme of environmental change to foster student creative thinking skills - Raudotul Ulum; Lukman Nulhakim; Adi Nestiadi (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
Creative thinking is one of the abilities that 21st-century students must possess. The importance of the ability to think creatively for students is so that students can spark ideas to find solutions in problem-solving. However, students' creative thinking skills still need to improve; this can be seen in the need for more active students in learning activities. Interactive learning media can attract students' attention so they can actively participate in learning activities. One application that can be used as a learning medium is Padlet. This study aims to analyze the efficiency level of Padlet-assisted interactive learning media with the theme of environmental change to foster the creative thinking abilities of class VII students. The method used is R&D (research and development) with a model that refers to Sugiono (2017), which is then modified and limited to the product trial stage. The result showed that the scores obtained on the validation and trial of Padlet-assisted interactive learning media were 94.25% in the